Microperimetry as a tool to assess retinal functional parameters in patients with recurrent macular hole - R.R. Fayzrakhmanov; E.A. Larina; O.A. Pavlovskiy (РМЖ "Клиническая офтальмология")
R.R. Fayzrakhmanov, E.A. Larina, O.A. Pavlovskiy N.I. Pirogov National Medical Surgical Center, Moscow, Russian Federation Aim: to assess functional parameters of the central retina using microperimetry in patients who underwent surgery for macular holes after prior procedures using free ILM flap peeling. Patients and Methods: 40 patients underwent surgery using free ILM flap peeling and autologous conditioned plasma to close macular hole. Examination was performed using MAIA microperimeter. Customized Expert Test mode (fixation point, fixation stability, fixation point shift during the examination) was applied. Macular integrity index was calculated. 12-point retinal sensitivity within 3 circles (small, medium, and large) was evaluated. Microperimetry was performed before the surgery and in the early and late postoperative periods. Results: after the surgery, fixation point gained physiological position in 70%, stable position in 80%, and relatively stable in 20% of patients. Higher macular light sensitivity was demonstrated in the late postoperative period (5 dB) as compared with the early postoperative period (3.01 dB). However, retinal light sensitivity tended to reduce insignificantly in the late postoperative period (to -1.065 dB) as compared with the early postoperative period. Conclusion: microperimetry is the key method of functional diagnosis to assess macular integrity as well as the efficacy of free ILM flap peeling technique using in patients with macular holes after prior surgery. Analysis of fixation point, fixation shift and stability as well as foveal light sensitivity evaluation are a valuable tool to assess vision quality and treatment efficacy. Keywords: retina, macula, macular hole, microperimetry, reoperation, free ILM flap peeling. For citation: Fayzrakhmanov R.R., Larina E.A., Pavlovskiy O.A. Microperimetry as a tool to assess retinal functional parameters in patients with recurrent macular hole. Russian Journal of Clinical Ophthalmology. 2020;20(2):51–55. DOI: 10.32364/2311-7729-2020-20-2-51-55.